Inconstitucionalidad del derecho de repetición de los obligados subsidiarios - Armijos Cabrera, Julia Macrina (2016)
The present thesis refers to the "Unconstitutionality of the Right of Repetition of those Forced Subsidiary", normative institution determined in the Code of the Childhood and Adolescence regarding subsidiary people that should lend foods, in special cases of foods where it is demanded the siblings, grandparents and uncles, they affect in its patrimonial, personal, economic, social and political goods; in our country; the right to the responsibility of passing foods is the progenitors' obligation as it determines it the Constitution of the Republic of the Ecuador, in the Art. 68 numeral 5to. that it points out the State it will promote the maternal and paternal corresponsabilidad and it will watch over the execution of the duties and reciprocal rights among mothers, parents, daughters and children. Therefore, alone to them it corresponds him, it passed foods and not to the relatives, this in corroboration with that prepared in the Art. 83 that it determines as duty and responsibility of the Ecuadorians to attend, to feed, to educate and to take care of the daughters and children. This duty is mothers' corresponsabilidad and parents in same proportion, and it will also correspond the daughters and children when the mothers and parents need it. These fundamental rights are harmed by the normative of the Art 5 (130) of the Code of the Childhood and Adolescence that he/she makes extensive the payment of foods to those forced subsidiary, and allowing them to follow a repetition action against the main one, to recover that paid. In this investigation work I intended to demonstrate the necessity that the State guarantees and protect; in the problem of the repetition action that affects to the harmony of the home, generating their disintegration.